Analisis Penggunaan Infografis sebagai Media Sosialisasi dalam Meningkatkan Pemahaman Masyarakat tentang Isu Lingkungan - Aldo Awali; Olvin Kristin Banamtuan; Ali Lukmansyah (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2025)
This study evaluates the effectiveness of using infographics in conveying environmental issues, such as waste management and climate change. Quantitative methods were used to measure the level of public understanding before and after exposure to infographics. The findings show that attractive and simple data visualization significantly increases public knowledge and awareness of the importance of environmental conservation.